Are bacteria responsible for aroma deterioration upon storage of the black truffle Tuber aestivum: A microbiome and volatilome study. (December 2019) - Vahdatzadeh, Maryam; Deveau, Aurélie; Splivallo, Richard
Abstract: Truffle fungi, luxurious food items with captivating aromas, are highly valued in the culinary world. However, truffles are perishable and their aroma undergoes deep changes upon storage. Additionally, truffle aroma might be partially derived from microbes. Hence, we investigated here the influence of storage on two factors, namely the volatile profile and bacterial community composition in the black truffle Tuber aestivum. The possible linkage among those factors was further explored. Our results demonstrate important changes in the volatile profiles of truffles over nine days of storage at room temperature. In the same time frame, dominant bacterial classes characteristic of fresh truffles ( α-Proteobacteria, β-Proteobacteria, and Sphingobacteria classes) were gradually replaced by food spoilage bacteria ( γ-Proteobacteria and Bacilli classes). Freshness and spoilage volatile markers (i.e. dimethyl sulfide (DMS), butan-2-one, 2- and, 2- and 3-methylbutan-1-ol, and 2-phenylethan-1-ol) were identified. Lastly, network analysis showed correlations between those markers and specific bacterial classes typical of fresh and spoiled truffles. Overall, our results demonstrate the profound effect of storage on the aroma and bacterial community composition of truffles and highlight how the gradual replacement of the commensal microbiome by spoilage microbes mirrors shifts in aroma profile and the possible loss of fresh truffle flavor. Highlights: The number of emitted volatiles strongly increases in truffles stored for a few days at room temperature. In the same timeframe, the commensal truffle microbiome is replaced by food spoilage/detrimental microbes. Strong correlations between microbiome and volatilome suggest that microbes could be driving changes in aroma. Identified freshness and spoilage volatile markers will permit to better define truffle quality and freshness.